1957
DOI: 10.1039/jr9570002545
|View full text |Cite
|
Sign up to set email alerts
|

495. Magnetic studies with copper(II) salts. Part II. Anomalous paramagnetism and δ-bonding in anhydrous and hydrated copper(II)n-alkanoates

Abstract: Martivl and Waterman. 2545 495. Hagnetic Studies with Copper(rr) Salts. Part lL1 Anomalous PaTamaCgnetimn and 6-Bondinq in Anhydrous and Hydrated Copper(n) n-AZknoates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
2

Year Published

1968
1968
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 0 publications
1
29
1
2
Order By: Relevance
“…Lifschitz & Rosenbohm (1915) found that its molar susceptibility was anomalously low compared with that of other copper salts. Guha (1951) and Figgis & Martin (1956) have reported the temperature variation of susceptibility for copper acetate, both hydrated and anhydrous, and Martin & Waterman (1957) reported similar measurements for various higher members of the series. All these compounds show a paramagnetic susceptibility which has a maximum at about 270 °K and which falls steeply with decreasing temperature.…”
Section: Introductionmentioning
confidence: 72%
“…Lifschitz & Rosenbohm (1915) found that its molar susceptibility was anomalously low compared with that of other copper salts. Guha (1951) and Figgis & Martin (1956) have reported the temperature variation of susceptibility for copper acetate, both hydrated and anhydrous, and Martin & Waterman (1957) reported similar measurements for various higher members of the series. All these compounds show a paramagnetic susceptibility which has a maximum at about 270 °K and which falls steeply with decreasing temperature.…”
Section: Introductionmentioning
confidence: 72%
“…3a) [9][10][11][12]. Ils confirment en fait 1'existence de complexes binucl6aires, dans la phase cristalline, pour les savons a chaine paraffinique longue, comme cela avait ddja ete sugg6rd par des dtudes magndtiques rdalisdes sur une sdrie de savons de cuivre [18][19][20][21].…”
Section: To Cite This Versionunclassified
“…A number of other copper(I1) carboxylates have magnetic properties similar to those of copper(I1) acetate monohydrate and it has been generally accepted that, provided agreement with eq. [l] is observed, these compounds have analogous binuclear structures (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%